CHOICE OF THE WAY OF PANCREATICODIGESTIVE FISTULA IN PANCREATICODUODENAL RESECTION - G. M. Barvanyan (Вестник хирургии имени И.И. Грекова)
The author offered an algorithm of definition of optimal ways of pancreaticodigestive fistula formation in pancreaticoduodenal resection. It is based on the following factors such as tissue conditions of the pancreas gland stump, a diameter of pancreatic duct and compliance with cut dimensions of gland stump of anastomotic loop of the jejunum. A comparative analysis of pancreaticodigestive fistulas performance was made in 2 groups. An algorithm of choice of pancreaticodigestive anastomosis was applied in the main group (n=35). An inconsistency of pancreaticodigestive fistula was noted in the main group (5,7%) and in the comparative group (n=59) - 17% (p=0,205). There weren’t any cases of destructive pancreatitis and lethality, which were directly specified by pancreaticodigestive anastomosis in the main group. Destructive pacreatitis developed in 10,1% cases in the comparative group. The lethality consisted of 5,1%. The results obtained confirmed the efficacy of individualized approach to formation of pancreaticodigestive fistulas and showed the practical value of investigation in this way.